1987
DOI: 10.3109/01460868709009017
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Camping: Effect on Knowledge, A Ttitude, and Self-Concept

Abstract: With the use of a pre-and posttest design, the effect of a one-week camping experience researched knowledge, attitude toward diabetes, and self-concept of diabetic and nondiabetic children in an integrated residential camp. Subjects for this study were 63 children with diabetes and 18 children without, ages 8 to 14. A modified Etzwiler Diabetic Knowledge Questionnaire, a modified Attitude toward Disabled People Scale, and a Piers-Harris Children's Self-concept Scale were administered on days one and six. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…No attempt was made to locate unpublished material or contact researchers for unpublished studies. A total of 18 studies met the criteria to be included in the review (Blau et al, 2002;Bluebond-Langner, Perkel, & Goertzel, 1991;Bluebond-Langner, Perkel, Goertzel, Nelson, & McGeary, 1990;Briery & Rabian, 1999;Kaplan, McKey, Toraya, & Moccia, 1992;Lord, Leger, Ridge, & Elisha, 2001;Meng, Tiernan, Bernier, & Brooks, 1998;Milliet, Carman, & Browne, 1996;Misuraca, Gennaro, Lioniello, Duval, & Aloi, 1996;Moffatt & Pless, 1983;Rew, 1987;Rubin & Geiger, 1991;Sawin et al, 2001;Semiz, Ozarslan, Bundak, & Bircan, 2000;Smith, Gotlieb, Gurwitch, & Blotcky, 1987;Smith, Schreiner, Brouhard, & Travis, 1991;Smith, Schreiner, Jackson, & Travis, 1993;Zimmerman et al, 1987).…”
Section: Search Strategies For Identification Of Studiesmentioning
confidence: 99%
“…No attempt was made to locate unpublished material or contact researchers for unpublished studies. A total of 18 studies met the criteria to be included in the review (Blau et al, 2002;Bluebond-Langner, Perkel, & Goertzel, 1991;Bluebond-Langner, Perkel, Goertzel, Nelson, & McGeary, 1990;Briery & Rabian, 1999;Kaplan, McKey, Toraya, & Moccia, 1992;Lord, Leger, Ridge, & Elisha, 2001;Meng, Tiernan, Bernier, & Brooks, 1998;Milliet, Carman, & Browne, 1996;Misuraca, Gennaro, Lioniello, Duval, & Aloi, 1996;Moffatt & Pless, 1983;Rew, 1987;Rubin & Geiger, 1991;Sawin et al, 2001;Semiz, Ozarslan, Bundak, & Bircan, 2000;Smith, Gotlieb, Gurwitch, & Blotcky, 1987;Smith, Schreiner, Brouhard, & Travis, 1991;Smith, Schreiner, Jackson, & Travis, 1993;Zimmerman et al, 1987).…”
Section: Search Strategies For Identification Of Studiesmentioning
confidence: 99%
“…The increase in self‐esteem for girl campers was statistically significant when compared with the non‐campers, although the girls at camp had the lowest self‐esteem scores at baseline. Zimmerman et al reported improvements in self‐concept for children with diabetes and those without diabetes at a 1‐wk camp (39).One study reported a decrease in global self‐worth among older campers (9th–10th grade) at 3 months, while a significant increase in global self‐worth at 3 months was reported for the youngest campers (2nd–5th grade) (3).…”
mentioning
confidence: 99%
“…The findings of our systematic review are based on 10 studies that evaluated the effectiveness of DSME interventions in recreational summer camps. [157][158][159][160][161][162][163][164][165][166] An additional five studies were identified but did not meet our quality criteria or did not report on relevant outcomes and were excluded from the review. [167][168][169][170][171] Study participants, identified as having type 1 diabetes, ranged in age from 8 to 15 years and were both male and female.…”
Section: Effectivenessmentioning
confidence: 99%